Correlation between micro-RNA-21 expression and inflammation cytokine in rabbits implanted with bare metal stent with the incidence of neo intimal hyperplasia - Hariawan, Hariadi; Soesatyo, Marsetyawan HNE; Munawar, Muhammad; Ghozali, Ahmad (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2019)
In-stent restenosis after stenting in vascular occurs secondary to the accumulation of smooth muscle cell and extracellular matrix. This condition is a major complication caused by the occurrence of neointimal hyperplasia (NIH). The study aimed to prove the role of miRNA-21 as a risk predictor of the NIH event in aorta of rabbits animal model who underwent bare metal (BM) type stent implantation and to know the miRNA-21 role in IL-6 and IL-8 expressions. This study was quasi experimental, coducted in Catheterization Laboratory Dr. Sardjito General Hospital Yogyakarta. Stent implantation was observed intravascular ultrasonography. Blood vessel which was already deployed by stent taken as sample for pathologic examination. Rabbit blood samples were collected on day 0, 7, and 28. Quantification miRNA-21 expression has been done with qPCR and ELISA approach. These 10 rabbits divided into two groups in which one group as control (without stent deployment, 4 models) and another group as intervention (with BM type stent deployment, 6 models). The increase in expression of miRNA-21 on the day 7 and day 28 in the intervention group compared to the control group. Neointimal hyperplasia increased in intervention group on day 7, and 28 were from mild grade to moderate, and severe respectively. In addition, levels of IL-6 and IL-8 increased on day 28 compared with on day 7. This study showed increase of miRNA-21 expression on day 7 and NIH rise from the mild to moderate. Furthermore, on day 28, that increases of miRNA-21 expression and NIH rose from to moderate to severe. The increase of miRNA-21 was also shown on day 7 and 28 followed by the increase of IL-6 and IL-8 levels.